2014
DOI: 10.1002/mop.28551
|View full text |Cite
|
Sign up to set email alerts
|

The design of a LTE/MIMO antenna with high isolation using a decoupling network

Abstract: A multi-input multi-output (MIMO) antenna with high isolation using a decoupling network for long term evolution (LTE) services is proposed. To improve the isolation, a decoupling network consisting of two sections of a transmission line is placed at the center of two radiating elements. The isolation was enhanced by approximately 23 dB comparing to that without a decoupling network. The fabricated MIMO antenna satisfies a 6-dB return loss requirement and the envelope correlation coefficient is maintained belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The achieved gain is 22.45-0.2 dBi. 27 A T-shaped strip was placed in ground plane to disturb the ground current to increase the isolation. The ECC of 0.002, gain of 2 dBi were achieved along with the omnidirectional radiation patterns.…”
Section: Decoupling Network Approachmentioning
confidence: 99%
“…The achieved gain is 22.45-0.2 dBi. 27 A T-shaped strip was placed in ground plane to disturb the ground current to increase the isolation. The ECC of 0.002, gain of 2 dBi were achieved along with the omnidirectional radiation patterns.…”
Section: Decoupling Network Approachmentioning
confidence: 99%
“…Various printed MIMO antennas designed for mobile terminals have been reported in recent years [2][3][4][5][6][7][8][9]. In [2], the proposed antenna resonates at multiple bands, which covers most 2G and 3G cellular frequency bands, some 4G LTE bands, WLAN, and Wimax bands.…”
Section: Introductionmentioning
confidence: 99%
“…Significant research efforts have been reported to reduce the mutual coupling [6][7][8][9][10][11][12][13]. A T-shape slot impedance transformer added to both single and dual band PIFA's resulted in an isolation better than 20 dB [6].…”
Section: Introductionmentioning
confidence: 99%
“…A decoupling network consisting of two sections of a transmission line is placed at the center of the two antenna elements in an LTE MIMO system is recently proposed [12]. The isolation was enhanced by approximately 23 dB comparing to that without a decoupling network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation